Strategi Implementasi Perubahan Organisasi di Era Digital untuk Meningkatkan Efisiensi dan Daya Saing pada PT. Barito Renewables Energy Tbk - Adytrio Reyhan Sudrajat; Guntur Haludin; Nouval Dwi Wicaksono; Alzetrho Baja Pratama; Muhammad Farrel Ardyanto; Mufadhal Daffa Dhiyaulhaq (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2025)
PT Barito Renewables Energy, Tbk (BREN) has emerged as one of the leaders in the renewable energy sector in Indonesia with a focus on diversifying energy sources, including solar and wind power development. The company utilizes advanced technologies such as Internet of Things (IoT) and Big Data to improve operational efficiency and reliability of energy supply. Through strategic partnerships with global companies and collaboration with the government, BREN contributes to Indonesia's clean energy transition. Funding through an Initial Public Offering (IPO) in 2023 successfully raised IDR 3.13 trillion in capital to support expansion and innovation. Commitment to sustainability is reflected in environmentally friendly projects and corporate social responsibility (CSR) programs that empower local communities. By continuously increasing production capacity and exploring new projects, BREN demonstrates real steps in change management that support business sustainability and competitiveness in the digital era. BREN's success serves as a model for other energy companies in facing global challenges and contributing to Indonesia's green energy transition.